Help-seeking Behavior of Disorders of Sex Development Patients in Palembang, Indonesia - Khairunnisa, Tyas Citra; Maritska, Ziske; Purnamasari, Septi; Zulissetiana, Eka Febri; Inggarsih, Rara (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Introduction. Disorders of Sex Development (DSD) is a congenital disorder in which there is atypical chromosomal, gonadal, or anatomical sex development. Children with DSD are often brought to the hospital too late for care due to limited knowledge about this condition among medical practitioners. Early diagnosis is important to improve prognosis and minimize complications and comorbidities of DSD patients. Methods. This study is a descriptive observational study with a cross-sectional approach through interviews and data collection from medical records of Dr. Mohammad Hoesin Palembang Hospital in 2020 - 2023. Results. In this study, it was found that the infancy age group (28 days - 1 year) was the most common age of arrival of patients to the hospital (29%) and the most common main complaint was clitoral enlargement (19.4%). Conclusion. This study found a wide variation in patients’ chief complaints, which makes the age of arrival of DSD patients to the hospital still quite late.